Synthesis of ZSM-5 Directly from Kaolin without Organic Template: Part-1: Effect of Crystallization Time - Hartanto, D.; Saputro, O.; Utomo, W.P.; Rosyidah, A.; Sugiarso, D.; Ersam, T.; Nur, H.; Prasetyoko, D. (Asian Journal of Chemistry, 2015)
Zeolite socony mobile-5 (ZSM-5) have been successfully synthesized directly from kaolin without using organic templates. ZSM-5 were synthesized by hydrothermal method at 175 °C with variation on crystallization time of 12, 24, 48 and 72 h. The molar composition of the zeolites was 10Na2O:100SiO2:Al2O3:1800H2O. The analysis of both from X-ray diffraction and FT-IR spectra showed that the ZSM-5 started to be formed during the crystallization time of 12 h. ZSM-5 with crystallization time of 24 h exhibit the highest crystallinity, about 101.17 % based on the reference. The crystallinity decrease on the crystallization time of 48 and 72 h. In addition, the surface morphology of ZSM-5 investigated by SEM showed that the sample with Si/Al ratio of 5.74-9.49 with variation time of 24, 48 and 72 h formed aggregate with a hexagonal crystal shape without sharp angle. However, the samples with crystallization time of 12 h showed irregular shape.